Jaringan Bonding Kapital Sosial Petani Melestarikan Mekanisme Adaptasi Kolektif Petani - Ica Wulansari (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
Farmers community neeed collective adaptive capacity to cope with climate change. The aimed of this research was to identify and analysis the network of social capital to preserve collective adaptation mechanism. This study adopted a qualitative approach to the type of descriptive. In analysing this research, the writer used coding analytics to find out the thematic category through social capital concept. The findings indicated that the bonding network of farmer was consist of access of knowledge, collective planning mechanism of planting paddy crop and formal institution of farmer groups. The bonding network had succeeded sustaining adaptive collective mechanism due to the existence of knowledgeable farmers. Meanwhile, this collective adaptive mechanism was strengthened by social interaction between farmer`s bonding network and bridging network. This interaction effectively to build collective planning capacity based on farmers group learning.